Influenza A Viral Infection with Septic Shock in Pregnancy - Soe Lwin; Myat San Yi; May Shi Leong; Haris Suharjono; Tin Moe Nwe (Case Reports in Obstetrics and Gynecology)
The influenza virus is RNA virus and is classified into four subtypes, influenza A, influenza B, influenza C, and influenza D. One of the subtypes of influenza A, the H1N1 strain, also known as swine flu, is especially of high risk for development of complications in pregnant women. The influenza A virus infection is difficult to diagnose clinically because its presenting symptoms are similar to those of the common cold but are more severe, last longer, and can be potentially life-threatening. This case also presented with common cold symptoms but her condition worsened later. Fortunately, obstetric health providers were vigilant enough to address the developing infection and its related complications. It was the cooperative effort of multidisciplinary team care which resulted in a favourable outcome in both mother and baby.